2012
DOI: 10.1101/gr.134437.111
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization of theBacillus cereussensu lato species: Backdrop to the evolution ofBacillus anthracis

Abstract: The key genes required for Bacillus anthracis to cause anthrax have been acquired recently by horizontal gene transfer. To understand the genetic background for the evolution of B. anthracis virulence, we obtained high-redundancy genome sequences of 45 strains of the Bacillus cereus sensu lato (s.l.) species that were chosen for their genetic diversity within the species based on the existing multilocus sequence typing scheme. From the resulting data, we called more than 324,000 new genes representing more tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
146
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(164 citation statements)
references
References 80 publications
(96 reference statements)
16
146
0
2
Order By: Relevance
“…The genome of the producer strain has been deposited in NCBI as a scaffold of 305 contigs (28). According to the NCBI entry, this sequence is located right at the 5= end of contig00045, which is separated by a gap from contig00074 (accession no.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genome of the producer strain has been deposited in NCBI as a scaffold of 305 contigs (28). According to the NCBI entry, this sequence is located right at the 5= end of contig00045, which is separated by a gap from contig00074 (accession no.…”
Section: Resultsmentioning
confidence: 99%
“…Information on the lantibiotic gene cluster of Bacillus pseudomycoides was accessed via the National Center for Biotechnology Information (NCBI; http://blast.ncbi.nlm.nih.gov/Blast.cgi) under the accession numbers CM000745 and ACMX01000000 (28). Subcellular localizations of the proteins were predicted using the online tool CELLOv.2.5 (subCELlular LOcalization predictor; http://cello.life .nctu.edu.tw/).…”
Section: Methodsmentioning
confidence: 99%
“…Of course, every strain has an array of other accessory modules for resistance, catabolism, etc., and if these were the focus of interest then biovars could be defined for these, too: each strain can belong to multiple biovars. This approach can readily be extended to other phenotypes in other bacteria, such as the very different pathogenicity phenotypes of the anthracis and thuringiensis biovars of Bacillus cereus [10], as we have argued elsewhere [3]. In a recent population genomics study, a previously unsuspected module for adaptation to serpentine soil was identified in Mesorhizobium by a genome-wide association approach [11].…”
mentioning
confidence: 96%
“…Bacillus cytotoxicus NVH 391-98, which was isolated from an outbreak of food poisoning (17), and B. cereus BAG5X-1, which was isolated from soil, are not related to the two groups. Other methods also identified the former strain as an outlier (18).…”
mentioning
confidence: 99%